Application of self-sealing vascular graft and expanded polytetrafluoroethylene vascular graft in establishment of vascular access - 肖光辉; 詹申; 王玉柱; 张丽红 (Linchuang shenzangbing zazhi)
Objective To compare application effects of self-sealing vascular graft(Acuseal) and expanded polytetrafluoroethylene(ePTFE) vascular grafts in establishment of arteriovenous fistula in maintenance hemodialysis patients, so as to provide reference for clinical selection of artificial vascular grafts.Methods A total of 108 patients, who were hospitalized to undergo vascular graft fistula surgery in Beijing Haidian Hospital from 1 October 2016 to 31 May 2018, were selected and divided into Acuseal group and ePTFE group based on types of vascular grafts. All patients were followed up to depletion of vascular accesses, patient death, lost of follow-up or the termination date of the study. First fistula puncture time and access-associated complications were compared in the patients between the two groups. Through Kaplan-Meier survival curve, primary patency and accumulative patency. Results A total of 108 patients were enrolled, with 55 ones in the Acuseal group and 53 ones in the ePTFE group. There is no difference of statistical significance between the patients in the two groups in age, sex, primary disease, dialysis age, drug use, related laboratory test indexes and internal diameter of anastomosed vessels. Compared to the ePTFE group, the mean puncture time for the Acuseal group was shorter, with(67.1+36.3)d vs(3.2+2.1)d respectively for the two groups(P<0.01). The 6-month/12-month primary patency values for the Acuseal and ePTFE groups were 58.2% vs 71.7%(P=0.14),and 32.7% vs50.9%(P=0.06); the primary accessory patency values, 67.3% vs 84.9%(P=0.06) and 54.5% vs 73.6%(P=0.07); the accumulative patency values, 96.3% vs 92.6%(P=0.23), and 85.5% vs 87.0%(P=0.66), with no statistically significant difference. The infection incidences for the Acuseal and ePTFE groups were 10.9% vs 3.7% respectively; the access-associated ischemia incidences, 3.6 vs 0 respectively; the pseudoaneurysm incidences, 0 vs 5.7%(P=0.07) respectively, with no statistically significant difference. In the Acuseal group 4 cases of lamination of vascular graft were observed.Conclusions Compared to the ePTFE vascular graft, the self-sealing vascular graft(Acuseal) allows for early access without compromising long-term patency or increasing the risk of complications, and so has value for clinical application.